BMDExpress 2: enhanced transcriptomic dose-response analysis workflow - Phillips, Jason R; Svoboda, Daniel L; Tandon, Arpit; Patel, Shyam; Sedykh, Alex; Mav, Deepak; Kuo, Byron; Yauk, Carole L; Yang, Longlong; Thomas, Russell S; Gift, Jeff S; Davis, J Allen; et al. (Bioinformatics, 2019)
Abstract Summary A new version (version 2) of the genomic dose-response analysis software, BMDExpress, has been created. The software addresses the increasing use of transcriptomic dose-response data in toxicology, drug design, risk assessment and translational research. In this new version, we have implemented additional statistical filtering options (e.g. Williams’ trend test), curve fitting models, Linux and Macintosh compatibility and support for additional transcriptomic platforms with up-to-date gene annotations. Furthermore, we have implemented extensive data visualizations, on-the-fly data filtering, and a batch-wise analysis workflow. We have also significantly re-engineered the code base to reflect contemporary software engineering practices and streamline future development. The first version of BMDExpress was developed in 2007 to meet an unmet demand for easy-to-use transcriptomic dose-response analysis software. Since its original release, however, transcriptomic platforms, technologies, pathway annotations and quantitative methods for data analysis have undergone a large change necessitating a significant re-development of BMDExpress. To that end, as of 2016, the National Toxicology Program assumed stewardship of BMDExpress. The result is a modernized and updated BMDExpress 2 that addresses the needs of the growing toxicogenomics user community. Availability and implementation BMDExpress 2 is available at https://github.com/auerbachs/BMDExpress-2/releases. Supplementary information Supplementary data are available at Bioinformatics online.